The Influence of Problem Based Learning Assisted by Interactive Worksheets on Critical Thinking Ability in Science Learning for Class V Students at SDN Batu Ampar 09 Pagi - Difah Nurfauziah; Mayarni (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to evaluate the impact of the Problem Based Learning model supported by Interactive Worksheets on students' critical thinking abilities in science learning. The research method used in this research is quasi-experimental. The research results show that the results of the Independent Sample t-test analysis show that there are differences in the posttest scores for the control class and the experimental class. This shows that the Problem Based Learning model has an influence on students' critical thinking skills at SDN Batu Ampar 09 Pagi. Increased critical thinking skills because the implementation of each PBL syntax was carried out in accordance with the design prepared by previous researchers which was demonstrated based on the results of observations.